6+11x=-21+x

Simple and best practice solution for 6+11x=-21+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+11x=-21+x equation:



6+11x=-21+x
We move all terms to the left:
6+11x-(-21+x)=0
We add all the numbers together, and all the variables
11x-(x-21)+6=0
We get rid of parentheses
11x-x+21+6=0
We add all the numbers together, and all the variables
10x+27=0
We move all terms containing x to the left, all other terms to the right
10x=-27
x=-27/10
x=-2+7/10

See similar equations:

| d/4−2=2 | | 6x+x+x-5-2=8+2x+x | | 1-10n=1 | | (3x-24)+2x+(4x+11)=180 | | d4− 2=2 | | 115=-4-7n | | 2x-3=12-123 | | 4a-3a=20+7 | | 8(x+7=6(x-4) | | 6x+x+x-5-2=8x+x | | -3.2+v/5=15.7 | | 12+x=x4 | | 20x+19=7x-15 | | -12.6x-4.9x=-154x=154 | | -9=4u+3 | | 2x/10=2 | | M14=3x+1 | | 10-7a=66 | | 5(h+1)=6(h-2) | | X2+4=(x+1)(x+3) | | x/7−14=-12 | | 5(4-x)=20-5x | | 82=9v+10 | | 4+15h+15=19+15h | | 0.75x+4=-5 | | -3z+4=-6z+28 | | -3=7-2g | | 129=1+8x | | -130=-10v-10 | | -7x-5=-6x-25 | | 12-4y=2y+11 | | -10(n-1)=30 |

Equations solver categories